If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 5)(x + 2) = 25 Reorder the terms: (5 + x)(x + 2) = 25 Reorder the terms: (5 + x)(2 + x) = 25 Multiply (5 + x) * (2 + x) (5(2 + x) + x(2 + x)) = 25 ((2 * 5 + x * 5) + x(2 + x)) = 25 ((10 + 5x) + x(2 + x)) = 25 (10 + 5x + (2 * x + x * x)) = 25 (10 + 5x + (2x + x2)) = 25 Combine like terms: 5x + 2x = 7x (10 + 7x + x2) = 25 Solving 10 + 7x + x2 = 25 Solving for variable 'x'. Reorder the terms: 10 + -25 + 7x + x2 = 25 + -25 Combine like terms: 10 + -25 = -15 -15 + 7x + x2 = 25 + -25 Combine like terms: 25 + -25 = 0 -15 + 7x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '15' to each side of the equation. -15 + 7x + 15 + x2 = 0 + 15 Reorder the terms: -15 + 15 + 7x + x2 = 0 + 15 Combine like terms: -15 + 15 = 0 0 + 7x + x2 = 0 + 15 7x + x2 = 0 + 15 Combine like terms: 0 + 15 = 15 7x + x2 = 15 The x term is 7x. Take half its coefficient (3.5). Square it (12.25) and add it to both sides. Add '12.25' to each side of the equation. 7x + 12.25 + x2 = 15 + 12.25 Reorder the terms: 12.25 + 7x + x2 = 15 + 12.25 Combine like terms: 15 + 12.25 = 27.25 12.25 + 7x + x2 = 27.25 Factor a perfect square on the left side: (x + 3.5)(x + 3.5) = 27.25 Calculate the square root of the right side: 5.220153254 Break this problem into two subproblems by setting (x + 3.5) equal to 5.220153254 and -5.220153254.Subproblem 1
x + 3.5 = 5.220153254 Simplifying x + 3.5 = 5.220153254 Reorder the terms: 3.5 + x = 5.220153254 Solving 3.5 + x = 5.220153254 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3.5' to each side of the equation. 3.5 + -3.5 + x = 5.220153254 + -3.5 Combine like terms: 3.5 + -3.5 = 0.0 0.0 + x = 5.220153254 + -3.5 x = 5.220153254 + -3.5 Combine like terms: 5.220153254 + -3.5 = 1.720153254 x = 1.720153254 Simplifying x = 1.720153254Subproblem 2
x + 3.5 = -5.220153254 Simplifying x + 3.5 = -5.220153254 Reorder the terms: 3.5 + x = -5.220153254 Solving 3.5 + x = -5.220153254 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3.5' to each side of the equation. 3.5 + -3.5 + x = -5.220153254 + -3.5 Combine like terms: 3.5 + -3.5 = 0.0 0.0 + x = -5.220153254 + -3.5 x = -5.220153254 + -3.5 Combine like terms: -5.220153254 + -3.5 = -8.720153254 x = -8.720153254 Simplifying x = -8.720153254Solution
The solution to the problem is based on the solutions from the subproblems. x = {1.720153254, -8.720153254}
| 5x^2+2Y^2+2xy-2x-4y+2=0 | | 4x+5+2x+12=180 | | 2x^2+5y^2=16 | | a^2+b^2=625 | | 7(z+3)-3z=44 | | 10+15y=3y | | Sin(3x)+sin(9x)= | | 9-y=15-5y | | 7-y=3-3y | | Sin(4x)cos(2x)= | | 4+3y=5y | | y=3x^2-17x+10 | | x*ln((8*x^3))+ln((8*x^2))=20-ln(2) | | 72=-16x^2+64x+12 | | 1x=8y+48 | | 2x/2-3x | | 0=-16x^2+64x+8 | | 2(f-3)=f+5 | | 100=60a+[40(2a)] | | -9=x(-10/x) | | 18x+6x-4x+2=2x-10x+16 | | 5x+5=4y-23 | | 2/7*3/8 | | Y-2=5(x-1)/3 | | 18-2x=12-5x | | y+w=c | | x^4y^2-4x^2y=0 | | 3x-3y-x^2y=0 | | 3p-7=14 | | 2x-4+45=4x | | 9-1.84= | | 2x-4=8x-2 |